Role of the PDZ Domain-Binding Motif of the Oncoprotein E6 in the Pathogenesis of Human Papillomavirus Type 31 - Lee, Choongho (American Society for Microbiology, 2004)
A number of PDZ domain-containing proteins have been identified as binding partners for the oncoprotein E6 of the high-risk type human papillomaviruses (HPVs). These include hDlg, hScrib, MAGI-1, MAGI-2, MAGI-3, and MUPP1. The PDZ domain-binding motif (-X-T-X-V) at the carboxy terminus of E6 is essential for targeting PDZ proteins for proteasomal degradation. The presence of this motif only in the high-risk HPVs suggests its possible role in HPV-induced oncogenesis. To investigate the role of the PDZ domain-binding motif of E6 in the HPV life cycle, two mutant HPV31 genomes were constructed: E6ValΔ, with a deletion of the last amino acid residue of E6 (valine), and E6ETQVΔ, with a deletion of the entire PDZ domain-binding motif of E6 (ETQV). Three human foreskin keratinocyte (HFK) cell lines were established which maintained transfected wild-type HPV31 or either of two mutant genomes. Cells containing either of two mutant genomes were significantly retarded in their growth rates and reduced in their viral copy numbers compared to those transfected with wild-type genomes. Western analysis did not reveal any significant changes in the levels of PDZ proteins following stable transfection of any HPV31 genomes into HFKs. Although the E6ETQVΔ-transfected HFKs exhibited a pattern of morphological differentiation that appeared different from the HPV31 wild-type-transfected HFKs in organotypic raft cultures, immunohistochemical analysis failed to identify substantial changes in the differentiation-dependent membrane localization of hDlg proteins. These results suggest that binding of E6 to PDZ proteins modulates the early viral functions such as proliferation and maintenance of the viral copy number in undifferentiated cells.